การวิเคราะห์องค์ประกอบเชิงยืนยันองค์กรความคล่องตัวในสถานศึกษา : Confirmatory Factor Analysis of Agile Organization in Schools - จันทกลิ่น, ธนกร; อารีรัตน์, วัลลภา; มาสาลี, นิทัสน์ (Journal of Humanities and Social Sciences (HUSOKKU), 2026)
This study aimed to 1) investigate the components and indicators of organizational agility in educational institutions, and 2) examine the consistency of the model of organizational agility components and indicators with empirical data. The study employed a mixed methods of research design. The first phase involved qualitative research through the analysis and synthesis of relevant concepts, theories, and related documents to develop the components and indicators. The second phase employed quantitative research to validate the empirical model. The research instrument was a five-point rating scale questionnaire with an overall reliability coefficient of 0.932 and an Index of Item-Objective Congruence (IOC) ranging from 0.67 to 1.00. Data were analyzed using the Mplus program. The findings revealed that organizational agility in educational institutions consisted of five main components and 14 indicators: 1) structural agility with three indicators, 2) agile leadership with three indicators, 3) customer-centered orientation with three indicators, 4) innovation and technology integration with two indicators, and 5) agile processes with three indicators. These components were consistent with relevant concepts and theories. The model fit analysis indicated that the model was consistent with the empirical data, with a chi-square value of 67.277, 52 degrees of freedom, a statistical significance level of 0.0755, and a Root Mean Square Error of Approximation (RMSEA) value of 0.032. The component with the highest factor loading was agile processes, followed by customer-centered orientation, agile leadership, innovation and technology integration, and structural agility, respectively. The findings suggest that the developed model is appropriate and can be applied as a conceptual framework for evaluating and developing organizational agility within the context of basic education institutions.